From Film to Files: Impact of Gerald Annan Photographic Collection - Gyasi Gyesaw, George (Ghana Library Journal, 2026)
Gerald Annan Forson’s photographic collection deposited at the J. H. Kwabena Nketia Archives offers captivating socio-political, economic, urbanization and cultural lifestyle of the Ghanaian people. The collection serves as an invaluable resource to students, scholars and the public. Annan Forson’s distinct techniques and skills offer a unique insight and clear details of capturing two decades of Ghanaian presidential history and socio-political movement. Inside the helm of the socio-political activities of government includes the change of government from military to civilian and from civilian to military, government projects, dignitary visitations and meetings, rallies and protest, elections and physical landscape of Ghana. However, this paper explores two case studies, one is the discovery of an old band named the Kyirem Cultural Band and St George’s International School learning experience at the J. H. Kwabena Nketia Archives. The photographic collection reawakened and connected the band again to exhibit their talent. On the other hand, the collection offered students from St. George’s International School a pictorial understanding of what was studied in class about government as a subject. Ultimately, Annan Forson’s unique collection is resource poise to inspire and learn from diverse group of ages.